2018
DOI: 10.7251/ghte1612001m
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Rosemary Essential Oil Applied Per Os on the Pharmacodynamic and Pharmacokinetic Properties of Paracetamol

Abstract: Introduction: Rosemary essential oil can be used for treating dyspepsia, mild spasmodic disorders of thegastrointestinal tract, externally as analgetic in muscular and articular pain and minor peripheral circulatory disorders.It is important to explore its analgesic potential and its influence on the pharmacodynamic and pharmacokineticproperties of paracetamol. Methodology: Rosemary essential oil was applied to mice orally (doses: 10 and 20 mg/kgb.w.) for pharmacodynamic tests for seven days. Rats treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…It was reported that many LABs can be applied for mushroom fermentation, including, Lp. plantarum [43][44][45][46][47][48][49], Lactobacillus delbrueckii subsp. bulgaricus, Levilactobacillus brevis, Lc.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that many LABs can be applied for mushroom fermentation, including, Lp. plantarum [43][44][45][46][47][48][49], Lactobacillus delbrueckii subsp. bulgaricus, Levilactobacillus brevis, Lc.…”
Section: Resultsmentioning
confidence: 99%